Predictors and mediators of European student teacher attitudes toward autism spectrum disorder. (March 2020) - Lindblom, Anne; Dindar, Katja; Soan, Sue; Kärnä, Eija; Roos, Carin; Carew, Mark T.
Highlights: The study provides empirical comparison across different settings; Teacher education in Sweden, Finland and England. Greater contact quality in practical placement significantly predicted more positive attitudes toward ASD. Perceptions of positive social norms toward ASD significantly predicted more positive attitudes toward ASD. Contact quantity or perceptions of course knowledge do not predict more positive attitudes toward ASD.